Hereditary colorectal cancer: genetics and screening diagnostics - O. I. Kit; D. I. Vodolazhsky; Yu. A. Gevorkyan; N. V. Soldatkina; F. N. Grechkin; M. A. Kozhushko; I. Yu. Yefimova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To present the data on main forms of hereditary colorectal cancer (CRC) and to discuss issues of its diagnostics, genetic testing and patient management. Summary. CRC is one of the most widespread oncologic diseases and takes the leading positions for morbidity and mortality in the pattern of neoplastic diseases in Russia. In 30% of cases disease development is associated to genetic predisposition, however only 5% of all CRC cases are linked to established hereditary syndromes, such as Lynch syndrome (hereditary non-polyposis colorectal cancer), family adenomatous polyposis, MUTYH-associated polyposis, juvenile polyposis, hereditary mixed polyposis syndrome, Peutz-Jeghers syndrome and serrated polyposis syndrome. The current review presents clinical and genetic features of two basic colorectal hereditary syndromes - Lynch syndrome and family adenomatous polyposis. Conclusion. Both clinical and molecular genetic investigations of hereditary CRC forms make possible individual comprehensive approach for diagnosis verification, evaluation of cancer risk, early diagnostics, treatment and prevention for decrease of morbidity and mortality.